TRPM7 overexpression enhances the cancer stem cell-like and metastatic phenotypes of lung cancer through modulation of the Hsp90α/uPA/MMP2 signaling pathway - Liu, Kai; Xu, Shao-Hua; Chen, Zhao; Zeng, Qing-Xin; Li, Zhi-Jun; Chen, Zhou-Miao (BMC cancer, 2018)
Waixenicin A, a bioactive extract of soft coral Sarcothelia edmondsoni, has been shown to be anti-neoplastic. However, its mechanisms of action remain unclear. Cancer stem cells (CSCs) and associated stemness factors are implicated in lung cancer. Here, we investigated the role of Waixenicin A on CSCs-like and metastatic lung cancer cells. We demonstrated and compared TRPM7 expression in the non-tumor lung tissues or bronchial epithelial 16-HBE cell line. TRPM7 was aberrantly expressed in the cancer tissues and SPCA-1, NCI-H520, SK-MES-1, A549 and 95D cell lines. Increased TRPM7 expression was associated with enhanced SOX2, KLF4, and CD133, Hsp90α, uPA, and MMP2 expression in lung cancer cells. TRPM7-silencing inhibited epithelial-to-mesenchymal transition (EMT), suppressed stemness markers and phenotypes, concomitantly suppressed Hsp90α/uPA/MMP2 axis. Coincidently, Waixenicin A treatment downregulated TRPM7 and oncogenic markers; Waixenicin A also attenuated the ability of lung cancer cells to form tumorspheres, in vitro. In validation, our clinicopathological analyses showed that a higher TRPM7 expression was positively correlated with the larger tumor size (p = 0.007), positive lymph node metastasis (p = 0.005) and disease grade (p = 0.003). Through its ability to inhibit Hsp90α/uPA/MMP2 signaling and suppress TRPM7 expression, we showed that Waixenicin A is a potential anticancer therapeutic agent for treating malignant lung cancer.